Isolated Horner Syndrome From an Elongated Styloid Process (Eagle Syndrome). Issue 4 (December 2015) - Chang, Caitlin A.; Lin, Tony; Fung, Kevin; Sharma, Manas; Fraser, J. Alexander
Abstract : Abstract: Eagle syndrome occurs when an elongated styloid process causes otolaryngological or neurological symptoms or signs. We report a patient who had an isolated asymptomatic Horner syndrome that resulted from a pinned internal carotid artery being dynamically injured by an elongated styloid process during chiropractic neck manipulation. There was no evidence of arterial dissection.